2022
DOI: 10.1038/s41419-022-04704-0
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitylase OTUD3 prevents Parkinson’s disease through stabilizing iron regulatory protein 2

Abstract: Iron deposits are neuropathological hallmark of Parkinson’s disease (PD). Iron regulatory protein 2 (IRP2) is a key factor in regulating brain iron homeostasis. Although two ubiquitin ligases that promote IRP2 degradation have been identified, the deubiquitylase for stabilization of IRP2 in PD remains undefined. Here, we report OTUD3 (OTU domain-containing protein 3) functions as a deubiquitylase for IRP2, interacts with IRP2 in the cytoplasm, de-polyubiquitylates, and stabilizes IRP2 protein in an iron-indepe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…OTUD3 has been identified as a tumor suppressor that is highly associated with tumorigenesis [ 41 , 42 ]. Our previous study found that OTUD3 knockout mice display motor deficits and nigrostriatal dopaminergic neurodegeneration, resembling the pathology of PD [ 5 ]. In the present study, we observed a significant increase in cell apoptosis after OTUD3 knockdown, consistent with our previous reports [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…OTUD3 has been identified as a tumor suppressor that is highly associated with tumorigenesis [ 41 , 42 ]. Our previous study found that OTUD3 knockout mice display motor deficits and nigrostriatal dopaminergic neurodegeneration, resembling the pathology of PD [ 5 ]. In the present study, we observed a significant increase in cell apoptosis after OTUD3 knockdown, consistent with our previous reports [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that OTUD3 knockout mice display motor deficits and nigrostriatal dopaminergic neurodegeneration, resembling the pathology of PD [ 5 ]. In the present study, we observed a significant increase in cell apoptosis after OTUD3 knockdown, consistent with our previous reports [ 5 ]. More and more evidence has shown that ER stress-induced apoptosis is an important cell death pathway for dopaminergic neurons [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations